2008
DOI: 10.1016/j.ydbio.2007.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Collagen XV, a novel factor in zebrafish notochord differentiation and muscle development

Abstract: Muscle cells are surrounded by extracellular matrix, the components of which play an important role in signalling mechanisms involved in their development. In mice, loss of collagen XV, a component of basement membranes expressed primarily in skeletal muscles, results in a mild skeletal myopathy. We have determined the complete zebrafish collagen XV primary sequence and analysed its expression and function in embryogenesis. During the segmentation period, expression of the Col15a1 gene is mainly found in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 44 publications
5
52
2
Order By: Relevance
“…Bioinformatic analyses indicated that this EST was most similar to a region of the collagen alpha-1 XV chain precursor (col 15a1) located in linkage group 2 (ENSEMBL database ENSDARG000000 61848, release 50). The sequence of the EST is, however, substantially different from that recently published for zebrafish col 15a1 [26], indicating that the EST-match represents for a novel duplicate of col 15a1 gene in the zebrafish, which we have named ''drCol 15a1b'' (to distinguish it from that previously described by [26], which we will now refer to as ''drCol 15a1a''). Comparison with the EST sequence did not fully characterize the open reading frame of drCol 15a1b, since it did not include the translation startpoint.…”
Section: Characterization Of a Novel Stem Cell Marker In The Zebrafishmentioning
confidence: 54%
See 4 more Smart Citations
“…Bioinformatic analyses indicated that this EST was most similar to a region of the collagen alpha-1 XV chain precursor (col 15a1) located in linkage group 2 (ENSEMBL database ENSDARG000000 61848, release 50). The sequence of the EST is, however, substantially different from that recently published for zebrafish col 15a1 [26], indicating that the EST-match represents for a novel duplicate of col 15a1 gene in the zebrafish, which we have named ''drCol 15a1b'' (to distinguish it from that previously described by [26], which we will now refer to as ''drCol 15a1a''). Comparison with the EST sequence did not fully characterize the open reading frame of drCol 15a1b, since it did not include the translation startpoint.…”
Section: Characterization Of a Novel Stem Cell Marker In The Zebrafishmentioning
confidence: 54%
“…As mentioned previously, the multiplexin family of collagens comprises the collagen XV (col 15a1) and XVIII (col 18a1), that in the case of zebrafish presents two duplicate sequences for each of the two genes: drCol 15a1a [26], drCol 15a1b (the one studied here), drCol 18a1 [27], and a novel sequence with high homology with col 18a1 (database access number ENSDARG00000041746), which has been discovered when searching the TreeFam database. Expression studies have revealed that drCol 15a1b shows a different expression pattern from those reported for drCol 15a1a and for drCol 18a1 in the zebrafish.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations